The role played by quasi-elastic and inelastic break-up of the 12C and 16O projectiles in the production of intermediate mass fragments at 14-35 MeV/u - Mira, Joele Paulus (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.